Draft Genome Sequences of 12 Mycolicibacterium smegmatis Strains Resistant to Imidazo[1,2-b][1,2,4,5]Tetrazines - Vatlin, Aleksey A. (Microbiol Resour Announc, 2019)
Here, we report 12 draft genome sequences of mutant Mycolicibacterium smegmatis strains resistant to imidazo[1,2-b][1,2,4,5]tetrazines, which are antituberculosis drug candidates. We have identified 7 different mutations in the MSMEG_1380 gene, which encodes the AcrR/TetR_N transcriptional repressor, which may activate efflux-mediated resistance.